HAEMATOLOGICAL AND BIOCHEMICAL PROFILE OF Clarias gariepinus FROM OPI LAKE IN NSUKKA LOCAL GOVERNMENT AREA, ENUGU STATE (FUDMA JOURNAL OF SCIENCES, 2023)
Haematological and biochemical analysis have been recognized as helpful tools for monitoring fish health. The objective of the study was to investigate the reference value for the haematological and the biochemical profile of Clarias gariepinus from Opi Lake, Nsukka Local Government Area of Enugu State, Nigeria.  A total of thirty samples of Clarias gariepinus comprising twelve males and eighteen females were obtained from the Lake. The blood samples were collected and analysed to obtain the haematological and biochemical parameters using standard methods. The results show that the haematological profile of Clarias gariepinus from Opi Lake were significantly different (p
Keywords: Haematology; Biochemistry; Clarias gariepinus; Opi Lake